2000
DOI: 10.1093/brain/123.12.2519
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ataxin-7 in normal human brain and retina

Abstract: Spinocerebellar ataxia 7 (SCA7) is a neurodegenerative disease caused by the expansion of a CAG repeat encoding a polyglutamine tract in the protein ataxin-7. We developed antibodies directed against two different parts of the ataxin-7 protein and studied its distribution in brain and peripheral tissue from healthy subjects. Normal ataxin-7 was widely expressed in brain, retina and peripheral tissues, including striated muscle, testis and thyroid gland. In the brain, expression of ataxin-7 was not limited to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 60 publications
5
51
1
Order By: Relevance
“…Because ATXN7 is widely expressed in humans (David et al, 1997;Cancel et al, 2000), but alterations are only observed in neurons, expression of the transgenes was targeted both ubiquitously using the da-GAL4 strain and in all neurons of the peripheral nervous system and CNS using the elav C155 -GAL4 line. To determine whether the truncated forms of human ATXN7 are expressed and processed normally in Drosophila, ATXN7T expression in the SCA7T-10Q and SCA7T-102Q da-GAL4 lines were analyzed on Western blots of larval extracts.…”
Section: Human Atxn7t Is Expressed and Processed Normally In Transgenmentioning
confidence: 99%
“…Because ATXN7 is widely expressed in humans (David et al, 1997;Cancel et al, 2000), but alterations are only observed in neurons, expression of the transgenes was targeted both ubiquitously using the da-GAL4 strain and in all neurons of the peripheral nervous system and CNS using the elav C155 -GAL4 line. To determine whether the truncated forms of human ATXN7 are expressed and processed normally in Drosophila, ATXN7T expression in the SCA7T-10Q and SCA7T-102Q da-GAL4 lines were analyzed on Western blots of larval extracts.…”
Section: Human Atxn7t Is Expressed and Processed Normally In Transgenmentioning
confidence: 99%
“…56,66 Indeed, a short N-terminal fragment of mutant ataxin-7 aggregates more readily than the full-length protein in transfected cells. 62 In addition, ataxin-7 inclusions arise exclusively in the nucleus, even in neurons with primarily Figure 7 SCA7 NI.…”
Section: -58mentioning
confidence: 99%
“…56 Hence, truncation of ataxin-7 might further promote its localization within the nucleus, where it perhaps exhibits faster aggregation and greater toxicity. Importantly, restricted occurrence of such proteolytic events might partly determine the selective patterns of neurodegeneration in SCA7.…”
Section: -58mentioning
confidence: 99%
“…Neuropathological examination reveals moderate to severe neuronal loss and gliosis in the cerebellum and associated structures (inferior olive, cerebellar cortex, dentate nucleus, pontine nuclei), the basal ganglia (globus pallidus, substantia nigra, subthalamic nucleus, red nucleus) and the spinal cord (Enevoldson et al, 1994;Gouw et al, 1994;Martin et al, 1994;Cancel et al, 2000). Spinocerebellar, olivocerebellar and efferent cerebellar tracts are severely affected.…”
Section: Neuropathologymentioning
confidence: 99%